2009
DOI: 10.2136/sssaj2008.0184
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl and Phenolic Humic Fractions Affect Pinus Nigra Callus Growth and Metabolism

Abstract: A humic substance was separated into carboxyl and phenolic fractions by affinity chromatography using a weak‐base amine resin. The humic extract and its fractions were analyzed for physical and chemical characteristics. Their biological effects were compared, at concentrations of 1 and 5 mg C L−1, on the growth of callus of Pinus nigra J.F. Arnold. A higher molecular weight and a greater degree of aromaticity were observed for the unfractionated humus and carboxyl fraction than for the phenolic fraction. Spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 72 publications
2
14
0
3
Order By: Relevance
“…However, humic acid at 1 g L −1 consistently inhibited the shoot growth of both hydroponic and soil-grown plants (Tables 1 and 2). It has been previously suggested that plant growth reductions by supra-optimal levels of humic acid may be related to the excessive chemical activity of small growth regulatory biomolecules released from humic acid agglomerates after interactions with organic acids in the rhizosphere (Piccolo et al 1996;Canellas et al 2002;Canellas et al 2008;Muscolo and Sidari 2009). …”
Section: Mechanisms By Which Humic Acid Affects Plant Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…However, humic acid at 1 g L −1 consistently inhibited the shoot growth of both hydroponic and soil-grown plants (Tables 1 and 2). It has been previously suggested that plant growth reductions by supra-optimal levels of humic acid may be related to the excessive chemical activity of small growth regulatory biomolecules released from humic acid agglomerates after interactions with organic acids in the rhizosphere (Piccolo et al 1996;Canellas et al 2002;Canellas et al 2008;Muscolo and Sidari 2009). …”
Section: Mechanisms By Which Humic Acid Affects Plant Growthmentioning
confidence: 99%
“…Effects of humic acid on plant development have generally been ascribed to the chemical effects of associated mineral nutrients or growth regulatory molecules. For example, a recent report by Muscolo and Sidari (2009) showed that known concentrations of a carboxylic fraction extracted from humic acid increased the growth of tissue cultured plant calli while a phenolic fraction at the same concentrations, reduced growth and even induced cell death. However, the concentrations and precise identities of any humic acid derived chemicals in the rhizosphere that may affect whole plant growth, have yet to be established (cf.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding values for humic acid extracts from thatch-mat fractionated as acid-detergent fi ber were 8.3 and 8.6, and those for acid-detergent lignin were 7.7 and 7.4. The E 4 / E 6 for unfractionated humus and its associated carboxylic and phenolic fractions were 3.04, 3.37, and 1.23 (Muscolo and Sidari, 2009), while those for humic acid after sequential adsorption to montmorillonite or kaolinite clays ranged from 7.79 to 5.24 (Wang and Xing, 2005). A high E 4 /E 6 indicates a smaller molecule that has less carbon but more oxygen and -CO 2 H groups and greater total acidity; there appears to be an inverse relationship between molecular weight and the E 4 /E 6 (Chen et al, 1977).…”
Section: Absorptionmentioning
confidence: 97%
“…Characterization and quantifi cation of functional groups, elemental composition, and other characteristics of OM has been accomplished with a variety of spectrographic methods (Mao et al, 2000;Dai et al, 2001;Stone et al, 2001;Narra et al, 2004Narra et al, , 2005Kinyangi et al, 2006;Muscolo et al, 2007;Baduel et al, 2009;Leinweber et al, 2009;Muscolo and Sidari, 2009). Specifi c absorbance with UV spectroscopy has been used extensively for the characterization of OM, especially of humic substances (Chen et al, 1977;Jaff rain et al, 2007).…”
Section: Absorptionmentioning
confidence: 99%
“…There are many data on the effectiveness of humic acids (HA) and preparations created on their basis in growth stimulation and improvement of resistance and productivity of different plant species. Thus, stimulating effect on plant growth has been demonstrated for low-molecular-weight fractions of HS and HA, in particular (Nardi et al 2002;Dobbss et al 2007;Canellas et al 2008;Muscolo & Sidari 2009), although it should be mentioned that biological activity of these substances may be better related to their chemical structure than to their molecular weight (Russell et al 2006;Muscolo et al 2007;Canellas et al 2008). It is of interest that the use of different methods, immunoassay being one of them, enabled identification of IAA in the chemical composition of HS (Muscolo et al 1998).…”
Section: Introductionmentioning
confidence: 99%